SIg-E- ("null-cell") non-Hodgkin's lymphomas. Multiparametric determination of their B- or T-cell lineage. - Knowles, D. M. (1985)
The authors performed immunophenotypic, functional, and molecular analysis of the neoplastic cells from 20 cases of SIg-, E-("null-cell") non-Hodgkin's lymphoma (NHL) in order to determine their lineage, better define this category of NHL, and evaluate the lineage specificity of selected phenotypic markers and the individual and collective utility of these approaches. They assigned 4 cases to the T-cell lineage, and 15 cases to the B-cell lineage, and 1 case remained indeterminant on the basis of immunophenotypic analysis. The cells from 2 cases assigned to the T-cell lineage expressed unusual phenotypes, but their T-cell derivation was confirmed by the demonstration of helper function in vitro. The 15 cases assigned to the B-cell lineage expressed a variety of B-cell-associated antigens, consistent with various stages of B-cell differentiation. Monoclonal antibodies OKT3, OKT4, OKT6, and OKT8 exhibited T-cell lineage restriction; and monoclonal antibodies OKB2, BL1, and B1 exhibited B-cell lineage restriction. Ia, TdT, cALLa, OKT9, and OKT10 exhibited lineage infidelity. Southern blot analysis for immunoglobulin heavy chain gene rearrangements confirmed 18 of the 19 lineage assignments made by immunophenotypic analysis and suggested that the 1 case of indeterminate phenotype was a B-cell neoplasm. One T-cell (OKT3+, T4+) neoplasm exhibited rearranged immunoglobulin heavy chain genes. Thus, neither immunophenotypic analysis nor the demonstration of rearranged immunoglobulin heavy chain genes alone permitted the satisfactory lineage assignment of every case of SIg-, E- NHL. However, combined immunophenotypic, functional, and genotypic analysis allowed us to assign every SIg-, E-NHL to the B- or T-cell lineage and to demonstrate that truly "null-cell" NHLs are probably very uncommon.